2021
DOI: 10.3329/jsr.v13i3.50647
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Lockdown and Changes of Air Quality in the Most Polluted City of Bangladesh

Abstract: Air pollution is now a serious issue all over the world. Especially, people of developing countries are seriously affected by air pollution because, like other pollution, air pollution is not given importance. Due to the covid-19 lockdown, pollution is reduced, and as expected, the air quality of Dhaka city has improved. Daily AQI data was collected for the months of April, May and June (2020) and compared with the last six years of data for these months respectively. It was found that the mean AQI of Dhaka ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Studies across the world showed drastic changes in pollution levels, especially in the air except ozone and its associated health benefits in the form of less mortality, morbidity, premature deaths, chronic obstructive pulmonary disease (COPD), disability-adjusted life years (DALY), etc. in lockdown periods [37][38][39]. The trend pattern of decreasing air pollution during the study period, 2020, was comparable to the similar period in 2019, but the magnitude of the decrease was more in 2020.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Studies across the world showed drastic changes in pollution levels, especially in the air except ozone and its associated health benefits in the form of less mortality, morbidity, premature deaths, chronic obstructive pulmonary disease (COPD), disability-adjusted life years (DALY), etc. in lockdown periods [37][38][39]. The trend pattern of decreasing air pollution during the study period, 2020, was comparable to the similar period in 2019, but the magnitude of the decrease was more in 2020.…”
Section: Discussionsupporting
confidence: 51%
“…The pre-lockdown phase (1st Feb 2020 to 22nd Mar 2020) data indicate Siliguri has poor air quality as compared to moderate air quality for Asansol, Howrah, and Kolkata. Pre-lockdown air qualities improved in the lockdown phase [37] and remained more or less the same in the unlocking phase. In pre lockdown phase, the pollution situation in Jadavpur, Rabindrasarobar, Asansol Court, and Padmapukur were similar and closely related, whereas Fort William and Belurmath were closely similar but distantly related.…”
Section: Discussionmentioning
confidence: 90%
“…It is very important to measure the wind speed and temperature structure in the boundary layer for studying the air-sea interaction and air pollution [25,26]. Low level wind shear directly impacts airplane flying safety and missile launching [27][28][29][30]. Therefore, CSIR-NPL developed a new SODAR system.…”
Section: Resultsmentioning
confidence: 99%